INFLUENCE OF CARBON AND NITROGEN ADDITION ON THE CORROSION RESISTANCE OF Co-28Cr-6Mo-0,8Si-0,8Mn-0,4Fe-0,2Ni ALLOYS - Fendy Rokhmanto; Cahya Sutowo; Ika Kartika (Widyariset, 2018)
Cobalt alloys is one of the implant materials that is used in orthopedic and dentistry, because of its biocompatibility, good mechanical properties, and high corrosion resistance. The mechanical properties and corrosion resistance can be enhanced by thermomechanical treatment and addition of alloying element. Carbon and nitrogen were added to enhance mechanical properties and high corrosion resistance. Effect of carbon variation and nitrogen to the corrosion resistance in Co-Cr-Mo (CCM) alloys were measured by corrosion measurement system (CMS) device in Hank’s Solutions after thermomechanical treatment process. Corrosion rate of Co-Cr-Mo alloys with carbon variation dropped to 5.8 x 10-4 mmpy and 5.2 x 10-4 mmpy with carbon variation and nitrogen. Decreasing corrosion rate indicated that the corrosion resistance of alloys is increased with the addition of carbon and nitrogen.